First stage in technological production of Stone Age animal teeth pendants: evidence from Zvejnieki (Latvia) and wider social implications - Aija Macāne; Kerkko Nordqvist; Kristiina Mannermaa; Andy Needham; Diederik Pomstra; Gabriel Cifuentes Alcobendas; Jānis Reblis; Ilga Zagorska; Aimée Little (Archaeological and Anthropological Sciences, 2025)
Animal teeth were amongst the most common materials utilised for personal ornament production during the Stone Age, especially in the Northern Hemisphere. The hunter-gatherer cemetery site of Zvejnieki (Latvia) (7500–2500 cal. BC) is a clear example of this, with more than 2000 animal teeth excavated from grave contexts. Animal tooth pendants from the site have received significant scholarly attention, largely focusing on their faunal identification, type of use, placement within graves, as well as aspects of their production. Considerably less attention, however, has been given to the process of extracting teeth and the corresponding physical traces this might leave behind. This is true for Zvejnieki, but also for teeth extraction for the purposes of personal ornamentation across early prehistory more generally. To address this gap, we have employed experimental archaeological methods to critically evaluate possible Stone Age techniques of tooth extraction from key ungulate species, assessing the diagnostic traces created on the tooth itself and on the skull or mandible. The results suggest that several different methods of tooth extraction are viable, but cooking animals using boiling or a pit method is highly efficient. These methods lead to high extraction rates with no tooth damage, while also rendering the meat from the skull edible and the bones usable for other applications, such as tool production. Our research provides insights into the relationships between different spheres of hunter-gatherer life and death at Zvejnieki, specifically the acquisition of game animals, their treatment, and how this interacts with the extraction and processing of materials for craftwork and food preparation.

An experimental study of wet-cooking in organic vessels: implications for understanding the evolution of cooking technologies - Andy Langley; Andy Needham; Roland Kröger; Gabriel Cifuentes-Alcobendas; Mette Adegeest; Jess Cousen; Christopher Lance; Hannah Benton; Amy-Rose Mansbridge; Amanda Satchell; Lewis Tomlinson; Francesca Rockall-Birtles; et al. (Archaeological and Anthropological Sciences, 2023)
The ability to control and direct fire is a major evolutionary step in the human story. The development of aceramic cooking technologies is less well understood as they rarely survive in the archaeological record. However, inferential evidence such as fire-cracked rocks, earthen pits and heated bones suggest a variety of cooking methods were used prior to the invention of ceramics. Yet there is a paucity of experimental evidence testing the efficacy of perishable organic containers in tasks involving their use with heat. The study presents experimental results of organic containers and their use for heating water related to cooking. Containers were made from deer hide and pig stomach and water was heated using two different techniques: placing the container directly above a fire and placing hot stones into the container. The results suggest that different organic containers and heating types could attain and maintain a sub-boiling cooking temperature; however, not all could reach boiling point. It is argued that these sub-boiling methods may be as, or perhaps more, desirable than boiling, with potential implications for the development of vessels prior to the adoption of ceramics.